The Desert Fathers' Beasts: Crocodiles in Medieval German Monastic Literature - Johannes Traulsen (Interfaces: A Journal of Medieval European Literatures, 2018)
This paper explores the literary representations of one of the most terrifying animals in the medieval imagination, the crocodile, in two monastic texts written in the German vernacular (Väterbuch, Alemannische Vitaspatrum). The literary figure of the crocodile in these religious texts combines ancient knowledge of crocodiles, biblical motifs, allegorical attributions and the lived experience of the Christian hermits, who encountered crocodiles as a part of their environment. Thus, crocodiles appear simultaneously as representations of divine power, as devilish beasts, as challenges to ascetic life in the desert, and as creatures miraculously tamed by the hermits' charisma. The ambiguous status of the desert as a space of temptation and redemption is thus reflected in literary representations of the crocodile, which in turn can be understood as a reflection on monastic life in general, intended for the medieval audience of the texts discussed.